Economic reformation of Ukraine: Historical and legal aspects - Svitlana Khomyachenko; Sergey Yuldashev (DANUBE: Law, Economics and Social Issues Review, 2020)
The purpose of this study is to analyze economic reforms conducted in Ukraine during the period of the state's independence. And also to identify, with the help of scientific tools - system analysis, management problems in the economy, their diagnosis, identification of the consequences that led to these problems, and ways development (at conceptual level) for their solving. The authors of the article proposed the concept of reforms in Ukraine. At the heart of the concept is the administrative reform aimed at creating organizational conditions under which corruption in power is almost completely neutralized. It is argued that such conditions are created by ensuring transparency, introduction of new information technologies, and minimizing the proportion of the so-called "human factor". Within the framework of the innovative project (model) of economic management, it is envisaged to redistribute central power between the central apparatus of economic management, local authorities and the non-state sector.
Keywords: 330; Transformations; Reforms; Law; Public Administration